The Impact of Chronic Periodontitis on Mother-Infant Bonding Status in Relation to Salivary Tumor Necrosis Factor Alpha and Interleukin-6 - Liqa S Hassan; Ban S Diab (College of Dentistry/ University of Baghdad, 2019)
Background: Chronic periodontitis is a bacterial infection that result in bone destruction associated with the increasing level of salivary tumor necrosis alpha and interleukin6 that affect Mother-infant bonding status. The aim of the present study was to assess the relationship between the Mother-infant bonding status in mothers with chronic periodontitis in relation to Salivary Tumor necrosis factor alpha and Salivary Interleukin6. Materials and Methods: The selected sample consisted of mothers with chronic periodontitis compared with mothers with healthy periodontium in postpartum period, their age ranged between 30-40 years. Both groups were subjected to postpartum Bonding Questionnaire (PBQ). Periodontal health status was assessed for control group like plaque index and gingival index in order to obtain control group with healthy periodontium, while measuring probing pocket depth and clinical attachment level in addition to plaque and gingival index for study group. Salivary Tumor necrosis factor alpha and Interleukin6 measure in saliva by enzyme-linked immune sorbent assay (ELISA). Results: The mean values of Salivary Tumor necrosis factor alpha and Interleukin 6 were found to be higher among mothers with chronic periodontitis than mothers with normal bonding relationship, and the percentage of disorder mother-infant bonding relation was higher in study group than in control group. Conclusion: Mother-infant bondings affected by chronic periodontitis as the patient have higher Salivary Tumor necrosis factor alpha and Salivary Interleukin6 than mothers with healthy periodontal condition.